The Excellent Sukoharjo District in Inclusive Health Services for People with Disabilities - Parahita, Justin; Suryawati, Chriswardani; Shaluhiyah, Zahroh (The Center for Disability Studies and Services Brawijaya University, 2021)
Sukoharjo district has Regional Regulation Number 18 of 2017 concerning Persons with Disabilities including Inclusion Health Services Policy. Problems completed during the implementation included four aspects that determined the success of policy implementation, they were communication between organizations, resources, disposition, and bureaucratic structure (standard operating procedures). Sukoharjo is the first district that has inclusive health service SOP. This research aims to analyze the implementation of the regional regulation which is an inclusive health service policy This qualitative research was conducted at Community Health Centers in Sukoharjo from May to December 2020. Data collection techniques were in-depth interviews, observation, and document study. Subjects consisted of 20 informants consisted of Community Health Center officers, staff of health office and social office, disability communities, and patients with disability. The results showed that the number of physiotherapist was insufficient, the budget for supplementary feeding and therapy equipment was insufficient, disability-friendly infrastructures in several community health centers still need repairment.